A Performance Analysis of Switched Capacitor Based Multilevel Inverter - Mahabharathi, S.; Sowkarthika, S. (Journal of Electrical Engineering and Automation, 2022)
A multilayer inverter based on Switched Capacitors (SC) using the Nearest Level Modulation (NLM) technique has been presented. To generate five levels, this multilevel inverter employs eight switches and two capacitors. The technique of nearest level modulation is used to provide a high-quality output voltage with low harmonic content. According to the simulation results, the expected inverter has lower Total Harmonic Distortion (THD) than a conventional inverter, using a voltage balancing control mechanism. The voltage on the DC-link capacitor is balanced using the NLM method. Through a SC-based inverter in the NLM approach, different voltage levels can be produced with a high voltage gain, resulting in less power outages, less turning stress, and better converter efficiency. As a result, no further devices are required to balance the voltage of both capacitors. The proposed system is simulated with MATLAB/SIMULINK, and its THD performance is tracked.